1987
DOI: 10.1172/jci113023
|View full text |Cite
|
Sign up to set email alerts
|

Neutral endopeptidase-like enzyme controls the contractile activity of substance P in guinea pig lung.

Abstract: The responsiveness ofisolated guinea pig lung parenchymal strips to substance P was enhanced by at least 100-fold in the presence of the endopeptidase inhibitors phosphoramidon (1 gM) or thiorphan (1 &M), but not with the converting enzyme inhibitor, captopril, or an inhibitor of serum carboxypeptidase N (both 1 t&M). Responses of guinea pig tracheal rings to substance P were also markedly potentiated by phosphoramidon. The increase in tissue responsiveness by these inhibitors was relatively specific for subst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
39
0

Year Published

1991
1991
2010
2010

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(41 citation statements)
references
References 37 publications
2
39
0
Order By: Relevance
“…NEP is a zinc-containing metalloendopeptidase involved in the degradation of several regulatory peptides and plays an important role in turning off peptide signaling events on the cell surface. 23,39,40 It is expressed on the surface of polymorphonuclear leukocytes and in several organs, including the kidney, in which it is localized, with a high density, on the brush border of proximal tubular CLINICAL RESEARCH www.jasn.org cells and on the cell surface of glomerular podocytes. 41,42 Debiec et al 42,43 showed that NEP may represent the target antigen in a rare subset of patients with alloimmune antenatal membranous nephropathy.…”
Section: Discussionmentioning
confidence: 99%
“…NEP is a zinc-containing metalloendopeptidase involved in the degradation of several regulatory peptides and plays an important role in turning off peptide signaling events on the cell surface. 23,39,40 It is expressed on the surface of polymorphonuclear leukocytes and in several organs, including the kidney, in which it is localized, with a high density, on the brush border of proximal tubular CLINICAL RESEARCH www.jasn.org cells and on the cell surface of glomerular podocytes. 41,42 Debiec et al 42,43 showed that NEP may represent the target antigen in a rare subset of patients with alloimmune antenatal membranous nephropathy.…”
Section: Discussionmentioning
confidence: 99%
“…These studies revealed that tachykinin and capsaicin receptor pharmacology is very similar in human and guinea pig airways, and in both species tachykinins are metabolized in the lung by neutral endopeptidase [253,[288][289][290][291]. Despite many important and fundamental discoveries relating to afferent nerve excitability, the axon reflex and tachykinin and capsaicin receptor pharmacology, it now seems likely that the axon reflex as it manifests in the lungs of guinea pigs and rats is not present in the human lung.…”
Section: Axon Reflexmentioning
confidence: 99%
“…This zinc metalloprotease cleaves a variety of bioactive peptides including tachykinins such as bradykinin and substance P (2,(4)(5)(6). CD1O/NEP downregulates neurogenic inflammation ofthe lung by modulating locally effective concentrations of tachykinins (7)(8)(9)(10). The enzyme has been found to hydrolyze bombesin-like peptides (BLPs) within the conserved seven amino acid terminus required for biological activity (reviewed in 11,12,13 ).…”
Section: Introductionmentioning
confidence: 99%